Growth and proliferation of caprine bone marrow mesenchymal stem cells on different culture media. (December 2020) - Jena, Dayanidhi; Kharche, Suresh Dinkar; Singh, Shiva Pratap; Rani, Sonam; Dige, Mahesh Shivanand; Ranjan, Ravi; Singh, Sanjay Kumar; Kumar, Harendra
Highlights: Three primary morphological cell shapes were observed. BMMSCs growth and proliferation was highest in MesenCult media at passage 0 (P0). BMMSCs growth and proliferation from P1 to P3 was highest in MesenPRO which yielded maximum cells (p < 0.05). Staining of BMMSCs with PKH26 resulted in a consistent, clear and uniform distribution of labelled cell membranes. Abstract: The growth and proliferation of mesenchymal stem cells are very sensitive in in vitro and a number of factors like media play a significant role in that context. In this study we assessed effect of different media on growth and proliferation of bone marrow derived mesenchymal stem cells (BMMSCs). The BMMSCs were isolated from caprine bone marrow and were subjected to magnetic activated cell sorting against CD90 +, CD105 +, CD271 + and CD34 − along with FC blocker. After characterisation, 2 × 10 4 cells were seeded in 12 well culture plates in four different media viz. MesenCult, MesenPRO, StemPro and complete DMEM (15 % FBS) to study their growth kinetic for 6 days from passage 0 (P0) to passage 3 (P3). The population doubling time (PDT) was derived from growth curve using logarithmic formula. The results showed that the BMMSCs growth and proliferation was highest in MesenCult media in P0 which varied significantly (p < 0.05) from rest of media and from P1 to P3, it was MesenPRO which yielded maximum cells (p < 0.05). The PDT was also in line with growth curve findings. In conclusion, the MesenPRO media had higher growth and proliferation rate from P1 to P3 although MesenCult had higher cell numbers in P0. In conclusion, the use of MesenPRO media could be a better option than conventional media when mesenchymal stem cells are used in clinical applications and other therapeutic purposes taking consideration to its higher growth and proliferation rate. And MesenCult would be a great option to harvest MSCs from P0.